2023
DOI: 10.1080/10717544.2023.2189118
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced therapeutic efficacy of doxorubicin against multidrug-resistant breast cancer with reduced cardiotoxicity

Abstract: Doxorubicin (DOX), a commonly used anti-cancer drug, is limited by its cardiotoxicity and multidrug resistance (MDR) of tumor cells. Epigallocatechin gallate (EGCG), a natural antioxidant component, can effectively reduce the cardiotoxicity of DOX. Meanwhile, EGCG can inhibit the expression of P-glycoprotein (P-gp) and reverse the MDR of tumor cells. In this study, DOX is connected with low molecular weight polyethyleneimine (PEI) via hydrazone bond to get the pH-sensitive PEI-DOX, which is then combined with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Due to the lack of a catalase in heart tissue and a weak antioxidant capacity, DOX.HCl can generate a significant amount of reactive oxygen species (ROS), leading to the indiscriminate movement of these radicals within the body, directly causing DNA strand breakage. Consequently, the mitochondrial DNA of cardiomyocytes is highly susceptible to damage by ROS [8,[60][61][62][63]. Hence, it is crucial to address the issue of eliminating excessive ROS produced by DOX.HCl during tumor cell eradication.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Due to the lack of a catalase in heart tissue and a weak antioxidant capacity, DOX.HCl can generate a significant amount of reactive oxygen species (ROS), leading to the indiscriminate movement of these radicals within the body, directly causing DNA strand breakage. Consequently, the mitochondrial DNA of cardiomyocytes is highly susceptible to damage by ROS [8,[60][61][62][63]. Hence, it is crucial to address the issue of eliminating excessive ROS produced by DOX.HCl during tumor cell eradication.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Guo et al [144] reported that EGCG effectively maintains YAP1 within the cytoplasm, enabling assembly of the ESCRT-III complex and ultimately stimulating autophagic apoptosis in BC cells. Alternatively, polyethylene glycol-doxorubicin/EGCG/folic acid inhibits the expression of P-glycoprotein (P-gp) and reverses the multidrug resistance (MDR) of BC cells, thereby enhancing therapeutic efficacy of doxorubicin [145]. Remarkably, paternal consumption of combined botanicals (SFN or EGCG-rich) contribute to the prevention of ER-negative mammary cancer in transgenic mice [123].…”
Section: Egcgmentioning
confidence: 99%
“…However, with the continuous advancement of antitumor drugs, chemotherapy remains the most crucial treatment for TNBC. Anthracycline drugs such as doxorubicin (DOX) are the foundation for breast cancer chemotherapy [ 5 ]. Although studies investigating de-anthracyclines have shown an equal short-term effect in the neoadjuvant stage, the long-term result remains unclear [ 6 ].…”
Section: Introductionmentioning
confidence: 99%